Persuasive Communication strategy of ustadz Ali Sati in increasing the enthusiasm for learning hadith knowledge of male students at the al Kautsar al akbar islamic boarding school in medan - azbar Rifa'i; Mukhtaruddin (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2024)
Three factors contribute to male students' decreased interest in studying Hadith at Pesantren Al Kautsar Al Akbar: the first is the lack of inventiveness on the part of ustadz in promoting learning, the harsh sanctions that are applied, and the dull Pesantren curriculum. Among the Ustad that instruct in the Al Kautsar Al Akbar Islamic Boarding School in Medan is Ustad Ali Sati. Pondok Pesantren Al Kautsar Al Akbar was founded in 1985 and is situated at 264 Jalan Pelajar Timur in Medan, North Sumatra. In this study, a qualitative, descriptive strategy was employed. Techniques for gathering data include recordkeeping, interviewing, and observation. Based on the study's findings, the researcher spoke with Ustadz Ali Sati, who shared information about persuasive communication techniques to boost male students' interest in studying hadith science at Al Kautsar Al Akbar Islamic Boarding School in Medan. The researcher also obtained the information required by the researchers, and the study's findings can be backed up by written data. In this discussion, the researcher provides an overview based on the research findings. In the implementation of Ustadz Ali Sati's communication strategy in increasing the enthusiasm for learning hadith science for male students, he has three models which are able to make students enthusiastic about learning hadith science: Constructivism Model, Cognitive Model, Jigsaw Model.